Estimating fast transient detection pipeline efficiencies at UTMOST via real-time injection of mock FRBs. Issue 2 (2nd December 2020) - Gupta, V; Flynn, C; Farah, W; Jameson, A; Venkatraman Krishnan, V; Bailes, M; Bateman, T; Deller, A T; Mandlik, A; Sutherland, A
ABSTRACT: Dedicated surveys using different detection pipelines are being carried out at multiple observatories to find more fast radio bursts (FRBs). Understanding the efficiency of detection algorithms and the survey completeness function is important to enable unbiased estimation of the underlying FRB population properties. One method to achieve end-to-end testing of the system is by injecting mock FRBs in the live data stream and searching for them blindly. Mock FRB injection is particularly effective for machine-learning-based classifiers, for which analytic characterization is impractical. We describe a first-of-its-kind implementation of a real-time mock FRB injection system at the upgraded Molonglo Observatory Synthesis Telescope (UTMOST) and present our results for a set of 20 000 mock FRB injections. The injections have yielded clear insight into the detection efficiencies and have provided a survey completeness function for pulse width, fluence, and dispersion measure (DM). Mock FRBs are recovered with uniform efficiency over the full range of injected DMs; however, the recovery fraction is found to be a strong function of the width and signal-to-noise ratio (SNR). For low widths (≲20 ms) and high SNR (≳9) the recovery is highly effective with recovery fractions exceeding 90 per cent. We find that the presence of radio-frequency interference causes the recovered SNR values to be systematically lower by up to 20 per cent compared to the injected values. We find that wider FRBs become increasingly hard to recover for the machine-learning-based classifier employed at UTMOST. We encourage other observatories to implement live injection set-ups for similar testing of their surveys.